Common Respiratory Disorders: Assessment And Management In Nursing Practice (Journal of Namibian Studies : History Politics Culture, 2022)
This article provides an overview of the assessment and management of common respiratory disorders encountered in nursing practice. Respiratory disorders, including asthma, chronic obstructive pulmonary disease (COPD), pneumonia, and respiratory infections, pose significant challenges to patient health and require prompt and effective nursing interventions. The article discusses key aspects of assessment, such as symptom evaluation, diagnostic testing, and monitoring, as well as evidence-based management strategies tailored to each disorder. Through interdisciplinary collaboration, patient education, and adherence to best practices, nurses play a critical role in optimizing patient outcomes and promoting respiratory health. The integration of comprehensive nursing care ensures that individuals with respiratory disorders receive holistic and patient-centered support throughout their healthcare journey.